O call center como um diferencial competitivo na estratégia de atendimento - Lima, Luciana da Silva (2014)
This thesis work aims to verify the importance of the call center within organizations, regardless of the market segment. Aims to analyze how the activity of call center can be crucial to determine the satisfaction or customer dissatisfaction with the company, and may be crucial to the customer is loyal to a company and become less susceptible to the actions of competitors. All content of this work was obtained through research and consultation with the works of various authors specialized mainly in call center, customer relationship marketing, satisfaction and loyalty. The research, as a method of obtaining data for the preparation of a study, is divided into typologies. To prepare this study was used as a descriptive research method in which, according Raupp (2008, p. 81), describing means to identify, report, verify. On the procedure to literature, which according to Gil (1999), is developed from theoretical frameworks as published books and articles was performed; and finally this research is qualitative approach as the type that Richardson (1999, p. 80) defines as that used to describe the complexity of a given problem as well as the deep understanding of its peculiarities. Observed these concepts, we can say that this job is suitable for dscrições authors. At the end of the study it is possible to identify that the call center industry, has been gaining increasing importance since the opening of the market occurred from the 1990s and the resulting increase in competition in various sectors. There is, including a socio-economic relevance of the sector, which since 2011 is the fastest in Brazil employs; having transformed the country into a global reference both in number of service positions and in quality in their best call centers. All sources consulted are unanimous in emphasizing that the call center, as one of the main points of contact between the customer and the company, constitutes a very valuable source of important information about the consumer and should be part of the service strategies and relationship developed by the companies. The study shows, however, that for the call center is a success factor the proper balance between technology, customer- oriented business processes and well-trained personnel should be observed, because these items are essential and complementary. The call center as a subject is vast and can be analyzed from various aspects, such as Technology, Human Development, Cost Management among others, but this study will analyze its basic activity, to suit the client, and its impact on the expectations and perceptions consumers